Thermophysical properties of stabilized copper oxide-polyaniline-palm oil based nanofluids - Nurhanis Sofiah, Abd Ghafar (2021)
Nanofluids have attracted boundless attention among researchers due to their excellent heat transfer properties and have been proposed for various advanced heat transfer applications. However, the use of excessive nanoadditives could be costly and pose a threat to the environment due to the high toxicity of recent used nanoparticles. The advancement in technology has forced the search for advanced heat transfer fluid to replace the non-renewable conventional mineral oil base fluids. Therefore, to propose more ecologically and cost-effective nanofluids, the possibility of conducting polymer as nanoadditives in vegetable-based heat transfer fluids is proposed and investigated. Palm oil (a vegetable-based oil) has been the preferred fluid to substitute the centuries-old oil in the present work. In this research, the inexpensive and environmentally friendly polymers, PANI nanofibers, were synthesized and hybridized with CuO nanoparticles to serve as nanoadditives in RBDL for nanofluid formulation. The stability of formulated nanofluids was evaluated as stability plays a vital role in ensuring the behavior of the thermal system at a designed parameter. The formulated nanofluids' thermophysical properties were investigated in greater depth to reveal the possibility as advanced heat transfer fluid. Mathematical equations were developed at the final stage of the research for future properties prediction. The two-step approach was espoused to formulate CuORBDL, PANI-RBDL, and CuO-PANI-RBDL nanofluid with different volume concentrations ranging from 0.01-0.5%. The morphology and structure of the synthesized nanoadditives were analyzed using TEM, EDX, XRD, FT-IR, and TGA. Meanwhile, sedimentation observation, DLS, UV-Vis, FTIR, TGA are performed for stability evaluation. Thermophysical properties of formulated nanofluids such as density, rheology, and thermal conductivity were measured using density meter, rheometer, and thermal analyzer instruments. The mathematical model was developed using RSM for future prediction and validation via comparison study with the present data. Morphological and structural analysis performed using TEM, EDX, XRD, FTIR, and TGA analysis revealed that the PANI nanofibers had been successfully hybridized with CuO nanoparticles. Sedimentation observation noticed that the CuO-RBDL achieved stability only for a week, while PANI-RBDL and CuO-PANI-RBDL samples maintain their dispersion stability near a month. The stability observation findings were supported and further inveterate by DLS and UV-vis analysis. All PANI-RBDL and CuO-PANIRBDL nanofluids samples achieved an absorbance drop in the range of 4 to 12% in 30 days from the UV-Vis analysis. The FTIR spectrum and TGA curve for all the nanofluids indicate that the prepared nanofluids are chemically and thermally stable. The density of all nanofluids was found to increase with the volume concentration of nanoadditives but decrease with temperature. All nanofluids' rheology properties were found to have Newtonian flow behavior, and the viscosity increases with nanoparticle volume concentrations, but their properties diminish with temperature increment. The most outstanding thermal conductivity properties achieved by nanofluid were the 10wt% CuOPANI nanocomposites with 31.34% enhancement, while the least thermal conductivity acquired is for CuO-RBDL with 17.8% enhancement. The experimental results were compared with the predicted result obtained from the mathematical model. All the plotted data were found to have good agreement with the experimental data indicating the developed mathematical model's reliability for response estimation. In summary, the formulated nano-enhanced RBDL nanofluid evaluated properties expose the possibility of alternative advanced heat transfer fluid for industrial application due to their superior inherent qualities.